Etiology and clinical characteristics of pediatric non-neoplastic posterior reversible encephalopathy: systematic review. Issue 3 (17th May 2022) - Jordão, Mariana; Raimundo, Pedro; Jacinto, Ruben; Garrido, Daniel; Martins, João; Estevens, Rui; Nogueira, Jerina; Fernandes, Emanuel; Macedo, Ana; Nzwalo, Hipólito
Abstract : Background: Although more commonly seen in adult population, posterior reversible encephalopathy syndrome (PRES) can also be observed in pediatric patients. The etiopathogenesis of pediatric PRES is poorly understood, and the available evidence comes mostly from childhood cancer. Analysis of the sociodemographic and clinical characteristics of the different noncancer-related types can improve the understanding of pediatric PRES. Methods: Systematic review of characteristics and outcome of noncancer pediatric PRES. Primary sources of investigation were identified and selected through Pubmed and Scopus databases. The research was complemented by reference search in relevant publications. Study protocol was registered (Prospero CRD42020165798). Results: We identified 449 cases of noncancer pediatric PRES from 272 studies, median age 10 (newborn to 17 years), 49.9% girls. The 4 most common groups of conditions were renal 165 (36.7%), hematologic 84 (18.7%), autoimmune 64 (14.3%), and cardiovascular 28 (6.2%) disorders. The 4 most prevalent precipitants identified were hypertensive crisis 119 (26.5%), corticosteroids 56 (12.5%), immunosuppression drugs 44 (9.8%), and biologic drugs 14 (3.1%). Clinical presentations included seizures 100 (22.3%), headaches 22 (4.9%), encephalopathy 17 (3.8%), visual disturbances 6 (1.3%), and focal deficit 3 (0.7%). The distribution of lesions was (n = 380): combined anterior/posterior circulation (40.8%), isolated posterior circulation (24.1%), anterior circulation (6.2%), and deep structures (1.6%). Residual neurological deficits occurred in about 1 out 10 cases. Conclusion: Pediatric PRES differs from the adult in etiology, precipitants, and clinical manifestations. Renal diseases predominate, acute raised blood pressure is less frequent, and cortical deficits are rarer. In addition, the proportion of patients with combined anterior/posterior circulation was higher. Permanent neurological sequels can occur.